Analisis Kebijakan Pemerintah Dalam Pendidikan Agama Dan Keagamaan Di Indonesia - Avif Alfiyah, Fitrah Sugiarto, Eva Sofia Sari, (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
The dynamics and paradigm of education in Indonesia has experienced a fairly dynamic development. This is the importance of education in particular getting more attention from the government, especially on the government policy system in developing religious and religious education. The presence of this paper tries to examine the basic aspects as the main issues studied as follows: 1) how are government policy regulations on religious and religious education. 2) how are the concepts and philosophical values, especially in the concept of policies carried out by the government on religious and religious education. This type of research is library research, namely library research through a study of books, journals, articles with relevant references. The research approach is descriptive analysis approach to analyze especially the concept of government policy in religious and religious education. Specifically, that the government seeks to provide policies in religious and religious education as efforts to develop students to understand and practice the values ​​of their religious teachings. Therefore, the existing religious and religious education policies in Indonesia so far have not had a negative impact on the existence of Islamic religious and religious education institutions.